A mitochondrial pentatricopeptide repeat protein enhances cold tolerance by modulating mitochondrial superoxide in rice - Xiaofeng Zu; Lilan Luo; Zhen Wang; Jie Gong; Chao Yang; Yong Wang; Chunhui Xu; Xinhua Qiao; Xian Deng; Xianwei Song; Chang Chen; Bao-Cai Tan; et al. (Nature Communications, 2023)
Abstract Cold stress affects rice growth and productivity. Defects in the plastid-localized pseudouridine synthase OsPUS1 affect chloroplast ribosome biogenesis, leading to low-temperature albino seedlings and accumulation of reactive oxygen species (ROS). Here, we report an ospus1-1 suppressor, sop10. SOP10 encodes a mitochondria-localized pentatricopeptide repeat protein. Mutations in SOP10 impair intron splicing of the nad4 and nad5 transcripts and decrease RNA editing efficiency of the nad2, nad6, and rps4 transcripts, resulting in deficiencies in mitochondrial complex I, thus decrease ROS generation and rescuing the albino phenotype. Overexpression of different compartment-localized superoxide dismutases (SOD) genes in ospus1-1 reverses the ROS over-accumulation and albino phenotypes to various degrees, with Mn-SOD reversing the best. Mutation of SOP10 in indica rice varieties enhances cold tolerance with lower ROS levels. We find that the mitochondrial superoxide plays a key role in rice cold responses, and identify a mitochondrial superoxide modulating factor, informing efforts to improve rice cold tolerance.